Time Variant Adjustment for The Solution of Control Point Unstability in Deformation Analysis of Borobudur Vertical Deformation Monitoring Network - Dwi Lestari; Yulaikhah Yulaikhah; Rizki Iman Sari (Jurnal Geospasial Indonesia, 2018)
Borobudur is Indonesian's cultural heritage which is recognized as a world heritage by UNESCO. As a world heritage structure, monitoring and maintenance have to be carried out periodically at Borobudur. Monitoring the vertical deformation of the temple using Geodetic method is one kind of monitoring which have to be done, in this case the monitoring uses leveling network. The design of leveling network at Borobudur in 2002 used absolute network, but the control point of this network has been indicated to be shifted. The control point displacement would cause a systematic error in the adjustment computation method for the analysis of vertical displacement. The correction of control point elevation due to the vertical shift is needed prior to the adjustment computation using observation model. In addition, there is a time variant adjustment computation method which able to calculate the vertical rate of object point displacement. This study aims to compare the vertical displacement analysis of the Borobudur’s vertical network from the adjustment computation using observation model with the correction of control point height and from time-variant adjustment method.Data used in this study were the elevation differences from leveling measurements in 2002, 2003 and 2004, and the elevation and vertical velocity of the control point in 2002. Adjustment computation using observation model began with the elevation correction of control point at each epoch. The adjustment computation was taken to determine the elevation of monitoring points at each epoch. Statistical test and vertical displacement analysis using significance parameter tests was carried out to analyze the results. Adjustment computation using time-variant method was taken to determine the elevation and the vertical velocity of the monitoring points at certain epoch intervals and validated using global test after the adjustment computation.The vertical displacement magnitude of Borobudur’s monitoring points, resulted from the parameter adjustment computation with the correction of control point compared to the time-variant adjustment results was differed in nanometer.  Time-variant adjustment computation method gave more accurates result of 1.5 times better than the observation model.